Formation of Contract in the Internet Under Islamic Law - Razali, Siti Salwani (2007)
The use of internet as a medium of communication or the trend of cyberspace contracting has widened the scope of contract formation. As the world of electronic commerce expands there is an increasing demand for clarity in the rules which apply to the participants and their transactions. Uncertainties that exist on many legal issues arise out of the online contract such as when or where the offer and acceptance is made, when the contract is concluded, whether agreements entered into electronically are enforceable and whether the display of goods in the web is considered as offer or not etc. Under Common law itself even though there are established rules regarding the online contract there are still a few unsettled issues regarding the online contract mainly because a standard international law governing the online contract is yet to be found. This is due to the fact that online contracts revolve around cross border transactions or the contract is beyond the jurisdictions of the respective countries. Therefore there is a great need for a standard international law. Under lslamic Law there are several areas of uncertainty which will havesignificant impacts on electronic contracting according to Shariah. The main areas are the issues of Majlis Aqad (Unity of Session). This is considered as a very fundamental issue especially in the online contract which implies the non physical presence of the parties. Similarly, Khiyar (Options) which is available to parties contracting inter presente will be an issue in the online contract. In fact if certain fundamental issues in the online contract are not resolved, then the dominance entry of the principles of gharar (uncertainty) will apply which will make online contracts-in lslamic Shariah not feasible . All other relevant areas to the online contract are discussed such as the issue of capacity and the doctrine of mistake (ghalaf). Therefore the study aims to review some of these fundamental notions and the formation of online contracts not only in Shariah law but also in Common Law, to achieve an acceptable degree of certainty that will enable the practice of online contract especially in Shariah. Furthermore, it is hoped that more practical principles of law governing the online contract can be established and be made applicable to all parties to the online contract